Reprogramming the body weight set point by a reciprocal interaction of hypothalamic leptin sensitivity and Pomc gene expression reverts extreme obesity - Kavaljit H. Chhabra; Jessica M. Adams; Graham L. Jones; Miho Yamashita; Martin Schlapschy; Arne Skerra; Marcelo Rubinstein; Malcolm J. Low (Elsevier, 2016)
Objective: A major challenge for obesity treatment is the maintenance of reduced body weight. Diet-induced obese mice are resistant to achieving normoweight once the obesogenic conditions are reversed, in part because lowered circulating leptin leads to a reduction in metabolic rate and a rebound of hyperphagia that defend the previously elevated body weight set point. Because hypothalamic POMC is a central leptin target, we investigated whether changes in circulating leptin modify Pomc expression to maintain normal energy balance in genetically predisposed obese mice. Methods: Mice with reversible Pomc silencing in the arcuate nucleus (ArcPomc−/−) become morbidly obese eating low-fat chow. We measured body composition, food intake, plasma leptin, and leptin sensitivity in ArcPomc−/− mice weight-matched to littermate controls by calorie restriction, either from weaning or after developing obesity. Pomc was reactivated by tamoxifen-dependent Cre recombinase transgenes. Long acting PASylated leptin was administered to weight-reduced ArcPomc−/− mice to mimic the super-elevated leptin levels of obese mice. Results: ArcPomc−/− mice had increased adiposity and leptin levels shortly after weaning. Despite chronic calorie restriction to achieve normoweight, ArcPomc−/− mice remained moderately hyperleptinemic and resistant to exogenous leptin's effects to reduce weight and food intake. However, subsequent Pomc reactivation in weight-matched ArcPomc−/− mice normalized plasma leptin, leptin sensitivity, adiposity, and food intake. In contrast, extreme hyperleptinemia induced by PASylated leptin blocked the full restoration of hypothalamic Pomc expression in calorie restricted ArcPomc−/− mice, which consequently regained 30% of their lost body weight and attained a metabolic steady state similar to that of tamoxifen treated obese ArcPomc−/− mice. Conclusions: Pomc reactivation in previously obese, calorie-restricted ArcPomc−/− mice normalized energy homeostasis, suggesting that their body weight set point was restored to control levels. In contrast, massively obese and hyperleptinemic ArcPomc−/− mice or those weight-matched and treated with PASylated leptin to maintain extreme hyperleptinemia prior to Pomc reactivation converged to an intermediate set point relative to lean control and obese ArcPomc−/− mice. We conclude that restoration of hypothalamic leptin sensitivity and Pomc expression is necessary for obese ArcPomc−/− mice to achieve and sustain normal metabolic homeostasis; whereas deficits in either parameter set a maladaptive allostatic balance that defends increased adiposity and body weight. Keywords: Body weight set point, Hypothalamus, Leptin, Leptin resistance, Obesity, PASylation, POMC